THE PROMOTION OF GAMIFICATION THROUGH ICT IN A VIRTUAL LEARNING COMMUNITY - Salazar Visurraga, Franklin Steve (2024)
The objective of the research is to analyze various bibliographic contributions in which the relationship of information and communication technologies (ICT) with the gamification process is identified to benefit a virtual learning community. The methodology used is based on the analysisof literary review. Categories were established to clarify the relationship of the main concepts, highlighting relevant aspects in the evolution of technologies and the way in which they led to the inclusion of innovative strategies, in order to enhance the teaching and learning process. As a result of the bibliographic review, a strong relationship between ICT and gamification in the educational field was determined, due to the evolution of resources that have emerged over time to connect the student more with their learning. It was concluded that gamification can be progressively incorporated into educational experiences, and that, apart from having components based on game mechanics, it can be a highly considered element in teaching, as a strategy that motivates students to engage more. with your learning. In addition, it was determined that a favorable level of knowledge of the teacher is required in relation to emerging technologies to propose scenarios that challenge the student in a virtual community.